Expansion of the world's deserts due to vegetation-albedo feedback under global warming - Zeng, Ning; Yoon, Jinho (Geophysical research letters, 2009)
Many subtropical regions are expected to become drier due to climate change. This will lead to reduced vegetation which may in turn amplify the initial drying. Using a coupled atmosphere‐ocean‐land model with a dynamic vegetation component that predicts surface albedo change, here we simulate the climate change from 1901 to 2099 with CO2 and other forcings. In a standard IPCC‐style simulation, the model simulated an increase in the world's ‘warm desert’ area of 2.5 million km2 or 10% at the end of the 21st century. In a more realistic simulation where the vegetation‐albedo feedback was allowed to interact, the ‘warm desert’ area expands by 8.5 million km2 or 34%. This occurs mostly as an expansion of the world's major subtropical deserts such as the Sahara, the Kalahari, the Gobi, and the Great Sandy Desert. It is suggested that vegetation‐albedo feedback should be fully included in IPCC future climate projections.